ANALISIS STUDI TATA KELOLA WISATA DALAM PERSPEKTIF GREEN TOURISM TERHADAP KESADARAN KONSERVASI DAN PARTISIPASI EKONOMI MASYARAKAT DI PANTAI TIRANG SEMARANG - Yohana Ivanka Lamtio Purba; Teguh Yuwono (Journal of Politic and Government Studies, 2026)
This study aims to analyze tourism governance from a green tourism perspective in relation to environmental conservation awareness and community economic participation in the Pantai Tirang tourism area, Semarang City. Current coastal tourism development not only focuses on increasing tourist visits but also emphasizes environmental sustainability and local community involvement in tourism-related economic activities. Pantai Tirang has the potential for environmentally based tourism development through mangrove conservation; however, its management still faces several challenges, including limited facilities, suboptimal environmental management, and insufficient coordination among managing actors. This study employs a descriptive quantitative approach using primary data collected through questionnaires distributed to 100 tourist respondents on a 1–5 Likert scale, and secondary data obtained through documentation and literature studies. Data analysis was conducted by calculating the mean value of each indicator, then classifying it using class interval analysis with a 0.8 interval width to determine assessment categories ranging from very poor to very good. Data were processed using Microsoft Excel and SPSS to ensure the validity and reliability of the research instruments. The results show that the mean score for tourism governance is 3.56, green tourism 3.77, community economic participation 3.81, and environmental conservation awareness 4.24. Based on class interval classification, tourism governance, green tourism, and community economic participation fall into the good category, while environmental conservation awareness falls into the very good category. The study concludes that the implementation of green tourism–based governance in Pantai Tirang has been relatively good but still requires improvements in environmental management, supporting facilities, and coordination among government, tourism managers, and local communities to support sustainable tourism development.